2021
DOI: 10.21273/hortsci15828-21
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Textural Characteristics of 23 Plum (Prunus salicina Lindl) Cultivars: Evaluation and Cluster Analysis

Abstract: Fruit textural characteristics can affect the storage, transportation, and processing of plum (Prunus salicina Lindl) in commercial production. We analyzed 23 plum cultivars with marked differences in fruit traits. Basic physicochemical indicators and textural characteristics of the fruits were determined using puncture testing and texture profile analysis. Furthermore, through the combined application of cluster analysis and principal component analysis, the indexes were simplified to three relatively indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…It has been reported that prolonged storage time leads to progressive degradation, resulting in a decrease in the overall sensory acceptability of fruit [ 32 ]. Texture measurement system analysis has high sensitivity and objectivity and has been applied to plums [ 20 ], dates [ 33 ], and apples [ 34 ]. In our experiment, four representative indicators including firmness, springiness, gumminess, and chewiness were obtained using TPA, and our results are consistent with the earlier report of Yang et al [ 35 ], who found that prolonged storage time would cause decreased springiness, hardness, viscosity, chewiness and viscosity of fruit ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that prolonged storage time leads to progressive degradation, resulting in a decrease in the overall sensory acceptability of fruit [ 32 ]. Texture measurement system analysis has high sensitivity and objectivity and has been applied to plums [ 20 ], dates [ 33 ], and apples [ 34 ]. In our experiment, four representative indicators including firmness, springiness, gumminess, and chewiness were obtained using TPA, and our results are consistent with the earlier report of Yang et al [ 35 ], who found that prolonged storage time would cause decreased springiness, hardness, viscosity, chewiness and viscosity of fruit ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each individual fruit was weighed on day 0 and after each sampling date during storage, and weight loss rate (WL) was expressed as a percentage (%). The texture profile analysis (TPA) was carried out following Qiu et al (2021) [ 20 ], with modifications, using a texture profile analyzer (TMS-Pilot, Ensoul Technology Ltd., Beijing, China). Springiness, firmness, gumminess, and chewiness were recorded ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Heatmap clustering, also referred to as hierarchical cluster analysis (HCA), stands out as a valuable multivariate analysis method, particularly adept at handling large datasets. This technique is instrumental in elucidating similarities among distinct data groups and effectively clustering those that share similarities [45]. Heatmap clustering has A large number of aromas of Occidental pears originate in the VOCs produced through fatty acid-derived pathways.…”
Section: Heatmap Clustering and Pcamentioning
confidence: 99%
“…Chinese plum (Prunus salicina Lindl.) is a common temperate fruit with a high economic value and is widely loved by consumers, but the content of lignin in the fruit affects its commercial value [18,19]. MT biosynthesis has the same regulatory factors as lignin biosynthesis, and exogenous MT treatment influences plant lignin synthesis [20].…”
Section: Introductionmentioning
confidence: 99%